My favorite mistake : an A circuit novel - Bloomberg, Georgina (Bloomsbury, 2012)
Teen equestrians Tommi, Kate, and Zara try to put aside thoughts of boyfriends and family issues as they continue to compete on the elite A-circuit, but secrets they are keeping from one another prove more problematic.